Methodologies for Improving HDR Efficiency - Liu, Mingjie; Rehman, Saad; Tang, Xidian; Gu, Kui; Fan, Qinlei; Chen, Dekun; Ma, Wentao (Frontiers in Genetics, 2019)
Clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9 (Cas9) system is a precise genome manipulating technology, which can be programmed to induce double-strand break (DSB) in the genome wherever is needed. After nuclease cleavage, DSBs can be repaired by nonhomologous end joining (NHEJ) or homology-directed repair (HDR) pathway. For producing targeted gene knock-in or other specific mutations, DSBs should be repaired by the HDR pathway. While NHEJ can cause various length insertions/deletion mutations (indels), which can lead targeted gene to loss its function by shifting open reading frame (ORF). Furthermore, HDR has low efficiency compared with the NHEJ pathway. In order to modify gene precisely, numerous methods came up by inhibiting NHEJ or enhancing HDR, such as chemical modulation, synchronized expression, and homology overlapping arm. Here we focus on the efficiency and other considerations of these methodologies.